Incorporating the burden of human sleeping sickness in an economic impact assessment of trypanosomiasis - Odiit, M.; Coleman, P.G.; Fèvre, Eric M.; Magona, J.; McDermott, John J. (International Society for Veterinary Epidemiology and Economics, 2000)
Tsetse-transmitted trypanosomosis is regarded as the most debilitating livestock disease in sub-Saharan Africa, responsible for annual economic losses of over US$1.3 billion. To date, however, all economic impact assessments of trypanosomosis have excluded the public health burden of the disease. Human trypanosomosis, known as sleeping sickness, is caused by Trypanosoma brucei gambiense and T b. rhodesiense, the former occurring in West and Central Africa and the latter restricted to East Africa with the predominant focus in South-East Uganda. Human trypanosomosis is a fatal disease if not treated. Current WHO estimates place the number of new cases per year, due to both parasites, across the whole of Africa, as high as 300,000 square. The burden of sleeping sickness may be expressed in terms of disability adjusted life years (DALYs), a generic health measure incorporating both mortality and morbidity and used to gauge the public health importance of different diseases. T.b. rhodesiense is a zoonotic disease, with the available evidence suggesting that rattle are the major reservoir of the disease in South-East Uganda and that controlling T b. rhodesiense in rattle could significantly reduce public health burden. Here, we use data on sleeping sickness patients in South-East Uganda to calculate the annual DALYs incurred due to T b. rhodesiense infection across Africa and within South-East Uganda.